Comparative study of soils - Smith, Walter Emory (My University, 1905)
Introduction: The comparative study of soils herein given is a physical study of five types of soil in their relation to Agriculture. This study has to do only with the relation of moisture and air to the soil. The comparisons given are found in experiments carefully preformed in the soil physics laboratory. Although field conditions were not obtained in the laboratory we found no conditions or results than which could not be applied directly to some phase of Agriculture. The moisture problem is one of great importance to farmers in the Middle West, and only by careful study of the physical conditions of the soil can the problem be solved. We must learn the conditions which aid in conserving soil moisture, and those which cause a loss, and practice farming methods which conserve the soil moisture. If certain conditions in the laboratory are influential in conserving moisture, like conditions in the field will produce similar effects. Eight experiments have been performed in the laboratory to demonstrate the difference in the relation of the five types of soil to soil moisture and air. In performing these experiments care was given to each soil. Also each soil had received the same treatment previous to experimenting. Each soil was air dried, and sifted so that of each type only .the fine soil was used. Experiment No. 1. Determination of the specific gravity of soils. This shows the weight of soils as compared with equal volumes of water There are two different kinds of specific gravity; real, and apparent. This is the real. Apparatus used in experiment:- A 100 c.c. flask with ground glass stopper, drawn out to an open capillary tube; another flask with distilled water; five samples of soil which had been dried at 110° C for 24 hours.
Citation: Smith, Walter Emory. Comparative study of soils. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Determining Specdific Gravity; Determining Hygroscopic Water; Specific Gravity of Pore Space; Theses